2016
DOI: 10.1002/cjce.22523
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of dialdehyde cellulose nanocrystal as an adsorbent for creatinine

Abstract: In this work, dialdehyde cellulose nanocrystals (DCNCs) were prepared via oxidizing cellulose nanocrystals (CNCs) with sodium periodate. The changes in the morphology of CNCs were evaluated by means of Fourier transform infrared spectrophotometry (FTIR), X‐ray diffraction (XRD), and atomic force microscopy (AFM). The product (DCNC) was used as an adsorbent for creatinine. The results showed that the adsorption capacity of DCNCs increased with the increase in its aldehyde content. With a decrease in the size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…The characteristics peak around 2900 cm −1 could be ascribed to the C–H vibration. Compared with that of BC, the spectrum of DABC shows a characteristic adsorption peak of carbonyl group at 1726 cm −1 , suggesting that aldehyde groups were introduced to BC to form DABC [39]. In the spectrum of HBP-g-BC, this peak of aldehyde group disappears, the peak of C–H vibration at 2921 moves to 2893 cm −1 , and there is a new characteristic peak at 1544 cm −1 , which could be assigned to the vibration of amine groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics peak around 2900 cm −1 could be ascribed to the C–H vibration. Compared with that of BC, the spectrum of DABC shows a characteristic adsorption peak of carbonyl group at 1726 cm −1 , suggesting that aldehyde groups were introduced to BC to form DABC [39]. In the spectrum of HBP-g-BC, this peak of aldehyde group disappears, the peak of C–H vibration at 2921 moves to 2893 cm −1 , and there is a new characteristic peak at 1544 cm −1 , which could be assigned to the vibration of amine groups.…”
Section: Resultsmentioning
confidence: 99%
“…Dialdehyde bagasse cellulose (DABC) was prepared according to Huang et al [39]. Coarse bagasse cellulose was firstly ground and purified by reaction with anhydrous sodium sulfate.…”
Section: Methodsmentioning
confidence: 99%
“…2b. In a comparison between cellulose and DAC spectra found that, cellulose showed adsorption bands of OH stretching at 3000-3500 cm −1 , and CH stretching at 2900 cm −1 , these peaks became narrow and deceased in DAC spectra [34]. The peak at 1640 cm −1 represents the OH bending of the adsorbed water in cellulose [13] while the peak at 1650 cm −1 in DAC spectrum represents the carbonyl group C=O of dialdehyde [35] sometimes this peak can be very small and hidden due to presence DAC in hydrated form but presence of hemiacetal peak confirms DAC formation [36].…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…The traditional methods like acid hydrolysis [4,7], enzyme-assisted hydrolysis [8] and mechanical treatments [9] can extract the CNs with hydroxyl groups, which are usually modified into other functional groups for further applications. Recently, CNs with functional groups (carboxyl or aldehyde groups) have been developed by 2,2,6,6-tetramethylpiperidinyl-1-oxyl (TEMPO) [10,11], ammonium persulfate (APS) [12], two-step approach combined acid hydrolysis and NaIO 4 oxidations [13][14][15], and one-step NaIO 4 oxidation [16]. The TEMPO and APS oxidations consume for a long time and the oxidizing agents are toxic [10,12] Abstract.…”
mentioning
confidence: 99%
“…cellulose nanocrystal (DACN) by two-step approach NaIO 4 oxidation, in which DACN with 50-376 nm in length and 3-18 nm in diameter were prepared by the sulfuric acid hydrolysis of fibers (cotton fibers and bleached softwood pulp) and then NaIO 4 oxidation [13][14][15]. However, the two-step approach NaIO 4 oxidation was complicated and needed environmental unfriendly acid hydrolysis process that leads to the low yield of DACN.…”
mentioning
confidence: 99%